Reduce marine debris policy in Indonesia. Issue 1 (April 2021) - Sari, D A A; Suryanto,; Sudarwanto, A S; Nugraha, S; Utomowati, R
Abstract: The massive use of plastic, from the production process to the disposal, will release a lot of greenhouse gas emissions into the atmosphere, which will exacerbate climate change. The large amount of plastic waste that can not be decomposed and eventually carried away into the sea is estimated to cause more plastic than fish in the ocean in 2050. Indonesia is the second-largest country in the production of marine plastic debris in the world after China. It occurs because of a misleading in waste management while still on land. Plastic debris in the marine will adversely affect the ecosystem in the sea and also the coastal. The reduction of marine debris will not run optimally if it is not supported by active involvement from the government, producers, and the community. This research was normative research based on primary and secondary legal materials. This study aimed to review the implementation of policies based on action plans to reduce marine debris. The result showed that with the baseline marine debris policy at 0.49 - 0.86 million tonnes/year, it required acceleration efforts from the government, producers, and the community to reduce marine debris by 70% by 2025.